Identification of Distinct Disease Activity Trajectories in Methotrexate‐Naive Patients With Rheumatoid Arthritis Receiving Tofacitinib Over Twenty‐Four Months. Issue 1 (30th December 2021) - Bykerk, Vivian P.; Lee, Eun Bong; van Vollenhoven, Ronald; Gruben, David C.; Fallon, Lara; Woolcott, John C.; Keystone, Edward
Abstract : Objective: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). To better understand tofacitinib treatment responses, we used group‐based trajectory modeling to investigate distinct disease activity trajectories and associated baseline variables in patients with active RA. Methods: This post hoc analysis used data from a phase III study of methotrexate‐naive patients receiving tofacitinib 5 mg twice daily. Changes in the 4‐variable Disease Activity Score in 28 joints, using the erythrocyte sedimentation rate (DAS28‐ESR) from baseline to month 24 were used in group‐based trajectory modeling to identify distinct disease activity trajectories. Patient and disease characteristics, changes in radiographic progression and patient‐reported outcomes, and safety up to month 24 were compared among trajectory groups. Results: From 346 methotrexate‐naive patients, 5 disease trajectory groups, defined by DAS28‐ESR scores, were identified, which progressed from high disease activity (HDA) to remission (group 1,  n = 28), to low disease activity (LDA) rapidly (group 2, n = 107), to moderate disease activity (group 3, n = 98), to LDA gradually (group 4, n = 46), or remained in HDA (group 5, n = 67), at month 24. At baseline, groups 1 and 2 generally had lower disease activity and more favorable patient‐reported outcomes, compared with other groups. Improvements in radiographic progression and patient‐reported outcomes over 24 months were generally consistent with DAS28‐ESR–predicted disease activity trajectories. Adverse event rates were generally comparable across groups. Conclusion: Distinct phenotypic subgroups identified heterogeneity in patients with RA normally analyzed as a single population. Trajectory modeling may enable separation of clinically meaningful subsets of patients with RA, and may help optimize treatment outcomes.